STUDI ATAS UKURAN DEWAN KOMISARIS INDEPENDEN DAN UKURAN KOMITE AUDIT INDEPENDEN TERHADAP KUALITAS AUDIT - Bennedik Hutapea (Fakultas Ekonomi Universitas Advent Indonesia, 2018)
The purpose of this study was to describe independent board size, independent audit committee size and audit quality on banking companies listed in Indonesia Stock Exchange. Another purpose of this study was to find out the significant effect of independent board size on audit quality and the effect of independent audit committee size on audit quality. The variables in this study are independent board size and independent audit committee size as independent variables and audit quality as the dependent variable. This study uses descriptive method with data processing using logistic regression. Sample method used was purposive sampling so this study used 35 banks as samples. Data obtained from annual reports of banking companies listed in Indonesia Stock Exchange during 2013-2015. The results showed that independent board size in banking companies already met requirements set by the OJK regulation. Independent audit committee size in banking companies still many who do not meet the conditions set by the OJK regulation and BI regulation. More than half banking companies used large audit firms (Big 4) that in view of giving a good audit quality. Another result of this study showed that independent board size have a significant effect on audit quality. Independent audit committee size have a significant effect on audit quality.